A conserved discrete unified gas kinetic scheme for microchannel gas flows in all flow regimes. (15th May 2018) - Liu, Hongtao; Cao, Yong; Chen, Qing; Kong, Mingchi; Zheng, Liang
Highlights: A conserved discrete unified gas kinetic scheme for gas microchannel flows in all flow regimes is developed. Direct and indirect discretization scheme for force term are introduced. Kinetic boundary conditions for both velocity and pressure fields are proposed. The model is validated by gas microchannel flows driven by shear stress, pressure, or external force in different flow regimes. Abstract: In this paper, a conserved discrete unified gas kinetic scheme (DUGKS) is developed for microchannel gas flows in all flow regimes, which has attracted much attention because of its basic research and wide engineering applications in the micro-electro-mechanical system (MEMS). In present DUGKS, distribution function and conservative variables are updated simultaneously to ensure the conservation of conservative variables. To study force-driven microchannel gas flow, the direct and the indirect discretization scheme for the force term are introduced, and their predictions in different flow regimes are further investigated. Meanwhile, to accurately realize the pressure boundary condition, a consistent linear extrapolation scheme is also presented. In this study, microchannel gas flows driven by shear stress, pressure, or external force have been investigated by present DUGKS. Numerical results, including velocity profile, non-linear pressure, and mass flow rate, agree fairly well with other benchmark in different flows regimes, which demonstrate the conserved DUGKS is a reliable method for microchannel gas flows.